To Studying the Consumer Attitude Towards Purchase Intention of Online Courses on Udemy Using Corelation with Reference to English Speaking and Excel Among Gen-Z in Ahmedabad - Chandni J. Vidani; Shashwat Sharma (MultiTech Publisher, 2023)
This research aims to examine the consumer attitude towards the purchase intention of online courses on Udemy among Gen-Z individuals in Ahmedabad, specifically focusing on English speaking and Excel courses. The study utilizes a correlation analysis to determine the connection between consumer attitudes and purchase intentions. The Gen-Z population, born between the mid-1990s and early 2000s, is known for its digital savviness and preference for online learning. As online education platforms like Udemy have gained significant popularity, it becomes crucial to understand the consumer attitudes that drive their purchase intentions. Additionally, English speaking and Excel courses are chosen as specific domains of interest due to their relevance in today's globalized and technology-driven world. To achieve the research objective, a survey questionnaire will be administered among a sample of Gen-Z individuals residing in Ahmedabad. The questionnaire will measure consumer attitudes towards online courses on Udemy, including factors such as Perceived utility, perceived convenience of use, course quality, and instructor trustworthiness are all factors to consider Respondents readiness to pay for English speaking and Excel classes will be used to determine purchase intent. Data collected from the survey will be analyzed using correlation analysis to examine the relationship between consumer attitudes and purchase intention. The findings will provide insights into the factors that influence Gen-Z's decision-making process when considering online course purchases on Udemy. The results of this research will be beneficial for online education platforms, course creators, and marketers to enhance their offerings and marketing strategies, ultimately catering to the needs and preferences of Gen-Z learners in Ahmedabad